Tinjauan Hukum terhadap Praktik Pengambilan Upah Jasa Fee pada Transaksi Agen Perbankan Syariah (Studi Kasus Layanan Perbankan Tanpa Kantor) - Teuku Mukhlisuddin (Multiverse: Open Multidisciplinary Journal, 2025)
This study examines the legal aspects of service fee collection practices carried out by Sharia banking agents within branchless banking services. The research is situated within the growing expansion of financial inclusion through agent-based banking systems that allow banking transactions to be conducted outside conventional bank offices. The study addresses the central question of whether the collection of service fees by Sharia banking agents is legally justified within the framework of Islamic law and Indonesian banking regulations. Employing a normative and comparative legal approach, the research analyses relevant regulatory frameworks, including Financial Services Authority Regulations concerning branchless financial services, as well as principles of Islamic commercial jurisprudence (muamalah). The study also considers practical cases of Sharia banking agent transactions to assess how fee mechanisms are implemented in practice. The findings demonstrate that the collection of service fees by agents is legally permissible under Islamic law when it is grounded in a valid contractual arrangement, particularly the wakalah bil ujrah contract, and when the fee structure is transparent, clearly determined, and free from elements of gharar (uncertainty) and riba (usury). These conditions ensure that the practice remains consistent with both Sharia legal principles and the regulatory framework governing Islamic banking services in Indonesia.